Clinical practices and attitudes regarding the diagnosis and management of heart failure: findings from the CORE Needs Assessment Survey. (18th September 2017) - Howlett, Jonathan; Comin‐Colet, Josep; Dickstein, Kenneth; Fuat, Ahmet; Pölzl, Gerhard; Delaney, Sean
Abstract: Aims: CORE is a continuing medical education initiative designed to support the evidence‐based management of heart failure (HF) in the primary and secondary care settings. The goal of the CORE Needs Assessment Survey is to describe current clinical practice patterns and attitudes among global stakeholders in HF care. Methods and results: The CORE Steering Committee guided the development of survey questions to assess clinical practice, confidence, and attitudes/perceptions among cardiologists, primary care physicians, and nurses involved in HF management. In total, 346 healthcare professionals from Australia ( n = 59), Austria ( n = 59), Canada ( n = 60), Spain ( n = 58), Sweden ( n = 52), and the UK ( n = 58) contributed survey data. Results revealed multiple gaps over the spectrum of HF care, including diagnosis (low recognition of the signs and symptoms of HF and limited use of diagnostic tests), treatment planning (underuse of recommended agents and subtherapeutic dosing), treatment monitoring and adjustment (lack of adherence to recommendations), and long‐term management (low confidence in providing patient education). Although primary care and specialist physicians and nurses shared common unmet needs, healthcare professional‐specific clinical gaps were also identified. Conclusions: The CORE Needs Assessment Survey provides timely data describing current clinical practices and attitudes among physicians and nurses regarding key aspects of HF care. These findings will be useful for guiding the development of interventions tailored to the specific educational needs of different provider types and designed to support the evidence‐based care of patients with HF.